BMSCs Interactions with Adventitial Fibroblasts Display Smooth Muscle Cell Lineage Potential in Differentiation and Migration That Contributes to Neointimal Formation - Y. Wendan; J. Changzhu; S. Xuhong; C. Hongjing; S. Hong; Y. Dongxia; X. Fang (Stem Cells International)
In this study a model of simulated vascular injury in vitro was used to study the characterization of bone-marrow-derived mesenchymal stem cells (BMSCs) morphology and to investigate the differentiation and migration of BMSCs in the presence of adventitial fibroblasts. BMSCs from rats were indirectly cocultured with adventitial fibroblasts in a transwell chamber apparatus for 7 days, and clonogenic assays demonstrated that BMSCs could be differentiated into smooth muscle-like cells with this process, including smooth muscle α-actin (α-SMA) expression by immunofluorescence staining. Cell morphology of BMSCs was assessed by inverted microscope, while cell proliferation was assessed by MTT assay. The expressions of TGF-β1, MMP-1, and NF-κB were detected by immunofluorescence staining and Smad3 mRNA was measured by reverse transcription PCR. Migration ability of BMSCs with DAPI-labeled nuclei was measured by laser confocal microscopy. Our results demonstrate that indirect interactions with adventitial fibroblasts can induce proliferation, differentiation, and migration of BMSCs that can actively participate in neointimal formation. Our results indicate that the pathogenesis of vascular remodeling might perform via TGF-β1/Smad3 signal transduction pathways.